Health and Wellness Product from Mangosteen (Garcinia mangostana L.) Rind: Bioactive Potentials - Nanjarajurs, Shashirekha M.; Dharmesh, Shylaja M.; Bhimangouder, Shivaleela V.; Eswaraiah, Mallikarjuna S.; Somasundaram, Rajarathnam (International Journal of Biotechnology for Wellness Industries, 2021)
Mangosteen rind (MSR) (Garcinia mangostana L.) is a predominant component of the fruit contributing to 62% of the whole fruit. However, utilization of the same for the preparation of health products was not explored due to its sensorially less acceptable parameters. Differential extraction in different polarity solvents of MSR was done and evaluated their acceptability for product preparation. Current study thus is a detailed investigation on bioactivity profiling of MSR fraction and utilization of the same for health product preparation. Among various extracts, 70% ethanol (70%AE) yielded the maximum (15g/100g). Xanthone:Phenolic ratio was 1: 2.8, in 70%AE as opposed to hot water extract – HWE and 50% AE, which contained Xanthone:Phenolic ratio of 1:1.4/5. Higher the phenolic content obviously reduces the bitterness of Xanthones. 70% AE contained phenolics 60.08± 0.213 mg/g and xanthones 22.56± 0.317 mg/g. HPLC analysis revealed a spectrum of phenolic acids such as gallic, chlorogenic, caffeic, epicatechin, catechin and ferulic acids at various levels. Potent Free Radical Scavenging (FRS) activity, cytoprotectivity, DNA protectivity, H+K+ATPase inhibitory (PPAI) activities were observed in 70% AE. Gallic/tannic acid appear to contribute to antioxidant activity; while ferulic acid was responsible for PPAI activity in 70%AE. Among xanthones, although α- mangostin was the dominating component, gartanin, 8 deoxygartanin and 3-isomangostin contributed to FRS activity. The products were prepared from 70%AE which are sensorially acceptable. Data thus for the first time delineate the specific health beneficial role of both phenolic and xanthone constituents in MSR particularly with higher abundance of phenolics than xanthones.